Implementation of the Green Constitution Concept in Local Regulations in Kudus Regency as an Effort to Support Sustainable Development - Dian Rosita; Naili Azizah; Zuniarti (Universitas Muhammadiyah Surabaya, 2025)
The Green Constitution concept emphasizes that environmental protection is a constitutional mandate that must be reflected in every legal policy, including regional regulations. This research aims to analyze to what extent the Green Constitution concept has been adopted in Kudus Regency regional regulations, while also assessing the effectiveness of regional regulations in supporting law enforcement and compliance with environmental regulations. This research uses normative and empirical juridical methods with a qualitative approach. Data was obtained through a review of legislation, literature studies, as well as observations and interviews with policy makers and stakeholders in Kudus Regency. The research results show that normatively, a number of regional regulations have included provision related to environmental preservation, especially in spatial planning and waste management. However, empirically, its implementation has not been optimal because it is still limited to administrative aspects, weak law enforcement, minimal coordination between institutions, and low community participation. Nevertheless, there are positive initiatives by local governments in integrating sustainability principles through community-based programs. Thus, the implementation of the Green Constitution concept in Kudus Regency requires strengthening of legal substance, harmonization of regulations, and strengthening of implementation capacity so that regional regulations do not stop as normative texts, but truly become effective and equitable instruments for environmental protection.